PCR-DGGE analysis for the identification of microbial populations from Argentinean dry fermented sausages - Fontana, Cecilia Alejandra (2005)
Different PCR-DGGE protocols were evaluated to monitor fermentation process and to investigate bacterial communities developed in two artisanal Argentinean fermented sausages. Bacterial universal primers frequently used in PCR-denaturing gradient gel electrophoresis (DGGE) were evaluated. Lactic acid bacteria (LAB) and staphylococci species isolated from Tucumán sausages were used to determine the experimental conditions for PCR amplification and DGGE differentiation. Total microbial DNA extracted directly from both fermented sausages was subjected to DGGE analysis. PCR-DGGE results were different for each set of primers used. Primers Bact-0124f(GC)-Uni-0515r and V1f(GC)-V1r showed to be efficient to differentiate LAB and Staphylococcus cultures while the set V3f(GC)-Uni-0515r allowed to demonstrate the succession of different Lactobacillus and Staphylococcus species during ripening process. An intense band corresponding to Lactobacillus sakei was observed to be present in both samples. Staphylococcus saprophyticus was only observed in Tucumán sausage while a band identified as Brochothrix thermophacta was detected in Córdoba sausage. PCR-DGGE analysis of different 16S rDNA amplicons was able to discriminate between LAB and Gram-positive, coagulase-negative cocci, resulting an effective tool to establish the microbiota developed in artisanal dry sausages.